2009
DOI: 10.2298/jsc0912359d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solvent and structure on the reactivity of 6-substituted nicotinic acids with diazodiphenylmethane in aprotic solvents

Abstract: The rate constants for the reactions of diazodiphenylmethane (DDM) with 6-substituted nicotinic acids in aprotic solvents at 30 °C were determined. The obtained second order rate constants in aprotic solvents, together with literature data for benzoic and nicotinic acids in protic solvents, were used for the calculation of solvent effects, employing the Kamlet-Taft solvatochromic equation (linear solvation energy relationship -LSER) in the form: log k = log k 0 + + sπ* + aα + bβ. The correlations of the kineti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…When the obtained correlation results were compared with the previously published results for the corresponding 6-substituted nicotinic acids, 10 it was found that the solvent effect disposition was similar considering the dominant HBA effect. However, the percentage values for the non-specific and the HBD interactions were different, as the proton-donor ability had a larger influence on the 6-substituted acids.…”
Section: Solvent-reactivity Relationshipsupporting
confidence: 52%
See 1 more Smart Citation
“…When the obtained correlation results were compared with the previously published results for the corresponding 6-substituted nicotinic acids, 10 it was found that the solvent effect disposition was similar considering the dominant HBA effect. However, the percentage values for the non-specific and the HBD interactions were different, as the proton-donor ability had a larger influence on the 6-substituted acids.…”
Section: Solvent-reactivity Relationshipsupporting
confidence: 52%
“…[1][2][3][4][5] Related to previous studies [6][7][8][9][10] of the chemical behavior of pyridinecarboxylic acid, the reactivity of 2substituted nicotinic acids with the following substituents Cl (chloro), OH (hydroxy), CH 3 (methyl), Br (bromo) and SH (mercapto) was studied in its reaction 570 DRMANIĆ, NIKOLIĆ and JOVANOVIĆ with DDM. [1][2][3][4][5] Related to previous studies [6][7][8][9][10] of the chemical behavior of pyridinecarboxylic acid, the reactivity of 2substituted nicotinic acids with the following substituents Cl (chloro), OH (hydroxy), CH 3 (methyl), Br (bromo) and SH (mercapto) was studied in its reaction 570 DRMANIĆ, NIKOLIĆ and JOVANOVIĆ with DDM.…”
Section: Introductionmentioning
confidence: 99%
“…By considering the equilibrium between the 2-pyridone and 2-hydroxypyridine tautomeric forms 15 in solvents of different polarity, it was found that increasing solvent polarity shifted the equilibrium towards the pyridone form. The effects of solvent dipolarity/polarizability and hydrogen-bonding on the absorption spectra of 3-cyano-4,6-diphenyl-5-(3-and 4-substituted phenylazo)-2--pyridones, and many other compounds, 17,18 can be interpreted by means of the linear solvation energy relationship (LSER) concept using a Kamlet-Taft Equation of the type: 19 ν = ν 0 + sπ* + bβ + aα 1, C).…”
Section: Solvent Effects On Absorption Spectra Of the Dyesmentioning
confidence: 99%
“…The 6-hydroxynicotinic acid, unlike the 2-hydroxynicotinic acid, gave a successful correlation in the same solvents, with the expected arithmetic signs of the coefficients: 6-Hydroxynicotinic acid: 22 log k = -1.92 + (2.37±0.36)π* + (1.99±0.09)α -(2.20±0.51)β (23) R = 0.982, s = 0.26, n = 5 Due to the ability of forming strong hydrogen bonds between the oxygen and nitrogen on both carboxylic acids and the hydroxyl group, both compounds are insoluble in many solvents; however, the set of five solvents given here, in which they both dissolve, was found. The 6-hydroxynicotinic acid, unlike the 2-hydroxynicotinic acid, gave a successful correlation in the same solvents, with the expected arithmetic signs of the coefficients: 6-Hydroxynicotinic acid: 22 log k = -1.92 + (2.37±0.36)π* + (1.99±0.09)α -(2.20±0.51)β (23) R = 0.982, s = 0.26, n = 5 Due to the ability of forming strong hydrogen bonds between the oxygen and nitrogen on both carboxylic acids and the hydroxyl group, both compounds are insoluble in many solvents; however, the set of five solvents given here, in which they both dissolve, was found.…”
Section: Various Solvents Containing No Hydroxyl Groupmentioning
confidence: 72%